PENGARUH ASIMETRI INFORMASI, LEVERAGE, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Fionissa Noor Rizki (AJAR, 2021)
This study aims to investigate the effect of information asymmetry on earnings management, investigate the effect of leverage on earnings management, investigate the effect of firm size on earnings management, and investigate the effect of profitability on earnings management. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2016-2018. The sample used was selected by the purposive sampling method and used secondary data in the form of an annual report. The analytical method used is multiple linear regression analysis to analyze the dependent variable, earnings management, and the independent variables are information asymmetry, leverage, firm size, and profitability. The results showed that information asymmetry did not have a significant impact on earnings management, but leverage, firmsize, and profitability had a positive and significant impact on earnings management.